Quantitative Easing in the Eurozone: a One-Year Assessment - Frank van Lerven (Intereconomics, 2016)
By pumping trillions of euros into the eurozone's financial system, the ECB's quantitative easing programme intends to indirectly alter the private sector's borrowing and spending behaviour. After more than a year since its initial inception, a review of the programme's impact reveals that policy makers should think twice before further expanding the programme–and could benefit from considering more direct ways of increasing spending in the real economy.
Keywords: 330; Quantitative Lockerung; Geldpolitische Transmission; Eurozone